IMPLEMENTASI PENGGUNAAN ANGGARAN DANA DESA DALAM PEMBANGUNAN INFRASTRUKTUR - Anita, Julia Sri; Fatmawati, Fatmawati; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the implementation of the village fund budget in supporting infrastructure development in Pattappa Village, Pujananting District, Barru Regency. This study uses a qualitative method with a descriptive type. The results of the research can be seen from 4 aspects, namely: (1) communication carried out by the village government with the community through socialization activities and village meetings is able to show that the village government has consistent attitudes and perceptions of SOP so that the community feels satisfied with the performance village government. (2) The resources owned by the Pattappa village government are good enough. (3) Disposition (disposition) related to the attitude of the implementer, the village government always tries to maximize the performance of village officials to improve the quality of good performance so that it has an impact on improving community welfare. (4) The bureaucratic structure of the village government in carrying out its duties must be in accordance with the basic performance measures and adapted to the existing understanding and procedures.